GLIDING DECREASE OF PRONOUNCING ENGLISH DIPHTHONG BY JAVANESE LEARNERS OF ENGLISH - Malikatul Laila; Hepy Adityarini (Universitas Muhammadiyah Surakarta, 2008)
The normal pronunciation of diphthong lies in putting the prominence or length to the nucleus vowel and gliding to the second one. However, this is not as the mostly phenomena of Javanese Learners of English (JLE)’s way of pronouncing diphthong. JLE tends to make shifts in pronouncing the quality of diphthong, one of which is a gliding decrease or omission. The data are collected by techniques of recording and demonstration. The data analysis uses techniques of comparing and contrasting be- tween JLE’s pronunciation and Received Pronunciation (RP). To amount of frequency in comparing JLE’s and RP, the percentage of the highest occurrence can be indi- cated. The result shows that JLE’s pronunciation of diphtong tends to reduce the fortis of nucleus before gliding or there is no gliding in the second vowel. Key words: sound shift, JLE, SPE, gliding, fortis, and pronunciation quality.